Immediate Breast Reconstruction With Concurrent Profunda Artery Perforator Flap and Autologous Fat Grafting - Pacifico Armando M. Cruz, MD; Hironobu Aoki, MD; Mariko Inoue, MD; Rei Ogawa, MD, PhD, FACS (Plastic and Reconstructive Surgery, Global Open, 2025)
Summary:. The profunda artery perforator (PAP) flap has become an important option in breast reconstruction, particularly for patients with prior abdominal surgery, insufficient abdominal tissue, or those who prefer to avoid abdominal scars. Despite its advantages, the PAP flap may be limited by insufficient volume relative to the size of the mastectomy defect. We present the case of a 64-year-old woman with scleroderma and a body mass index of 20.9 kg/m² who was diagnosed with right breast cancer. She underwent a nipple-sparing mastectomy and sentinel lymph node biopsy, followed by immediate reconstruction using a PAP flap harvested from the left posteromedial thigh. To complement the flap, fat was harvested from the flap periphery and injected into the pectoralis muscle and subcutaneous space to enhance contour and shape. Postoperatively, the patient experienced no complications, with no evidence of flap compromise, necrosis, or donor site issues. She expressed satisfaction with the reconstructed breast volume and contour, and the unnoticeable donor site scar. This case demonstrated the benefits of combining PAP flap reconstruction with autologous fat grafting to achieve sufficient breast volume and contour, particularly in patients with low body mass index or challenging tissue conditions. The synchronous use of microvascular reconstruction and regenerative techniques maximizes outcomes, avoids secondary procedures, and provides a viable solution for immediate breast reconstruction. Further research is needed to validate the long-term efficacy of this combined approach.